Quality of Service in bandwidth adapted hybrid UMTS/WLAN interworking network - R. Shankar; P. Danajayan (Universitas Ahmad Dahlan, 2019)
Integration of Universal Mobile Telecommunications System (UMTS) and Wireless Local Area Network (WLAN) result in ubiquitous connection for end users. In the integrated network, ensuring the quality of service to users and enhancing capacity of network are prominent issues. Bandwidth adaptation technique is one of the solutions to overcome these issues. Bandwidth adaptation based on per flow and per class schemes were proposed for loosely coupled interworking network. In this paper, hybrid coupled UMTS and WLAN interworking network is analyzed with bandwidth adaptation based on per flow and per class schemes and the performances have been compared. Simulation result shows that the proposed hybrid coupled interworking network with bandwidth adaptation based on per class scheme performs better with enhanced quality of service and network capacity.